Ectoparasitic Effects of Citronella Grass (Cymbopogon nardus) and Lemongrass (Cymbopogon citratus) Shampoo Against Mites (Dermanyssus gallinae) of Native Chickens (Gallus gallus domesticus) - Antonio, Lindy Joy; Estudillo, Sinamar E. (Future Science / FSH-PH Publications, 2023)
This study was conducted to produce an herbal shampoo using the extracts of citronella grass, lemongrass, and mixed of both grasses. It was conducted to find out which among the produced herbal shampoos was the effective against red mites of native chicken and their time observed to kill mites. In addition, it was conducted to determine the cost analysis of using the different grasses as a shampoo. Sixty laying native chickens naturally infested with mites were used in the study the chickens were grouped randomly and distributed to five (5) treatments. Herbal shampoos were prepared before bathing the native chickens; the bathing process was begun and lasted for four (4) weeks with seven (7) days interval. Over all the positive control or the commercial shampoo Wash Out Intense® was the most effective among all other treatments with 92.83% efficacy. The notable efficacy of the commercial shampoo was followed by the herbal shampoo produced which was the citronella shampoo then the lemonella shampoo followed by lemongrass shampoo, with 76.14%, 71.14%, and 68.80% efficacy respectively. The treatment that shows the lowest observed time to kill mites was the positive control (Wash Out Intense®) which consist the effective components to kill mites, it was then followed by T3 the citronella shampoo, T5 the lemonella shampoo and lasty T4 the lemongrass shampoo. Lastly the cost analysis of making shampoo using citronella, lemongrass and mixed of both grasses’ extracts revealed that were less economical than the commercial shampoo available.